Diamond films : chemical vapor deposition for oriented and heteroepitaxial growth - Kobashi, Koji (London : Elsevier, 2005)
Discusses the most advanced techniques for diamond growth Assists diamond researchers in deciding on the most suitable process conditions Inspires readers to devise new CVD (chemical vapor deposition Ever since the early 1980s, and the discovery of the vapour growth methods of diamond film, heteroexpitaxial growth has become one of the most important and heavily discussed topics amongst the diamond research community. Kobashi has documented such discussions with a strong focus on how diamond films can be best utilised as an industrial material, working from the premise that crystal diamond films can be made by chemical vapour disposition. Kobashi provides information on the process and characterization technologies of oriented and heteroepitaxial growth of diamond films.